Chromosomal radiosensitivity of triple negative breast cancer patients. (2nd November 2019) - Francies, Flavia Zita; Herd, Olivia; Cairns, Alan; Nietz, Sarah; Murdoch, Marshall; Slabbert, Jacobus; Claes, Kathleen B. M.; Vral, Anne; Baeyens, Ans
Abstract: Purpose: Based on clinical and molecular data, breast cancer is a heterogeneous disease. Breast cancers that have no expression of estrogen receptor (ER), progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2) are defined as triple negative breast cancers (TNBCs); luminal cancers have different expressions of ER, PR and/or HER2. TNBCs are frequently linked with advanced disease, poor prognosis and occurrence in young African women, and about 15% of the cases are associated with germline BRCA1/2 mutations. Since radiotherapy is utilized as a principle treatment in the management of TNBC, we aimed to investigate the chromosomal instability and radiosensitivity of lymphocytes in TNBC patients compared to luminal breast cancer patients and healthy controls using the micronucleus (MN) assay. The effect of mutations in breast cancer susceptibility genes on chromosomal radiosensitivity was also evaluated. Methods: Chromosomal radiosensitivity was evaluated in the G0 (83 patients and 90 controls) and S/G2 (34 patients and 17 controls) phase of the cell cycle by exposing blood samples from all patients and controls to 2 and 4 Gy ionizing radiation (IR). Results: In the G0 MN assay, the combined cohort of all breast cancer, TNBC and luminal patients' exhibit significantly elevated spontaneous MN values compared to controls indicating chromosomal instability. Chromosomal radiosensitivity is also significantly elevated in the combined cohort of all breast cancer patients compared to controls. The TNBC patients, however, do not exhibit enhanced chromosomal radiosensitivity. Similarly, in the S/G2 phase, 76% of TNBC patients do not show enhanced chromosomal radiosensitivity compared to the controls. In both the G0 and S/G2 phase, luminal breast cancer patients demonstrate a shift toward chromosomal radiosensitivity compared to TNBC patients and controls. Conclusions: The observations of the MN assay suggest increased chromosomal instability and chromosomal radiosensitivity in South African breast cancer patients. However, in TNBC patients, the irradiated MN values are not elevated. Our results suggest that the healthy lymphocytes in TNBC patients could handle higher doses of IR.